Harmonizing Civic Disposition and Local Culture: Language Politness in Classroom Management Based on TIDAR Values - NOVITASARI; MASHUD SYAHRONI; WINASTI RAHMA DIANI; FIRDA AULIA IZZATI (Jurnal Moral Kemasyarakatan, 2026)
Harmonizing Civic Disposition and Local Culture: Linguistic Politeness in TIDAR-Value-Based Classroom Management. Civic Education (PKn) in higher education faces a paradox between a democratic academic environment and a crisis in student communication ethics. This study offers a novel contribution by applying a micro-pragmatic perspective to civic disposition, positioning lecturers as "ethics managers" who integrate politeness theory and local TIDAR values ​​into classroom management. Employing an exploratory qualitative case study design at Universitas Tidar, the research utilized participant observation, in-depth interviews, and document analysis, interpreted through Brown and Levinson’s politeness theory and the Miles and Huberman analysis model. The results indicate that positive and negative politeness strategies dominate student speech, whereas lecturer strategies remain reactive. While students understand TIDAR values, these values ​​have not yet been systematically implemented in classroom management practices or the curriculum. These findings serve as the foundation for developing an ethics-based, participatory classroom management model.